Government response to ultra-processed and sugar beverages industries in developing nations: The need to build coalitions across policy sectors - Gómez, Eduardo J. (International Food Policy Research Institute, 2023)
How were the governments of three middle-income countries with high levels of non-communicable diseases (NCDs)—India, Mexico, and South Africa—able to implement sugar-sweetened beverage taxes (SSBs) despite intense opposition from powerful corporations? Employing a multiple streams analytical framework to explain the agenda-setting process, this chapter highlights several factors that generated supportive coalitions for SSBs, including the importance of transnational advocacy in each country as well as governments’ interest in generating more revenue from the tax. By contrast, regulatory measures to regulate the soda and snack food industries, such as limits on advertising, sales, and food labeling, have been less accepted by the same governments. To explain why, the chapter argues that coalitions around these policies are weaker, regulation generates lower levels of public contestation and visibility, and the prospect for generating government revenue is less pronounced.